One year of SARS-CoV-2 circulation in the Nouvelle-Aquitaine region, February 2021–2022, France - Deroche, Luc; Bellecave, Pantxika; David, Romain; Ouattara, Eric; Garcia, Magali; Roblot, France; Boinot, Laurence; Faucher, Jean-François; Rejasse, Aurélie; Gschwind, Guillaume; Malvy, Denis; Filleul, Laurent; et al. (Frontiers in Microbiology, 2023)
Background Since 2021, 3 variants of concern (VOC) have spread to France, causing successive epidemic waves. Objectives To describe the features of Alpha, Delta and Omicron VOC circulation in the Nouvelle-Aquitaine region, France, between February 2021 and February 2022. Study design Data from the three university hospitals (UH) of Nouvelle-Aquitaine were used to describe regional SARS-CoV-2 circulation (RT-PCR positive rates and identified VOC) as well as its consequences (total number of hospitalizations and admissions in intensive care unit). They were analyzed according to the predominant variant and compared with national data. Results A total of 611,106 SARS-CoV-2 RT-PCR tests were performed in the 3 Nouvelle-Aquitaine UH during the study period. The 37,750 positive samples were analyzed by variant-specific RT-PCR or whole-genome sequencing. In 2021, Alpha VOC was detected from week 5 until week 35. Delta became the most prevalent variant (77.3%) in week 26, reaching 100% in week 35. It was replaced by Omicron, which was initially detected week 48, represented 77% of positive samples in week 52 and was still predominant in February 2022. The RT-PCR positive rates were 4.3, 4.2, and 21.9% during the Alpha, Delta and Omicron waves, respectively. The ratio between intensive care unit admissions and total hospitalizations was lower during the Omicron wave than during the two previous waves due to the Alpha and Delta variants. Conclusion This study highlighted the need for strong regional cooperation to achieve effective SARS-CoV-2 epidemiological surveillance, in close association with the public health authorities.